2020
DOI: 10.3390/life10060084
|View full text |Cite
|
Sign up to set email alerts
|

On the Potential of Silicon as a Building Block for Life

Abstract: Despite more than one hundred years of work on organosilicon chemistry, the basis for the plausibility of silicon-based life has never been systematically addressed nor objectively reviewed. We provide a comprehensive assessment of the possibility of silicon-based biochemistry, based on a review of what is known and what has been modeled, even including speculative work. We assess whether or not silicon chemistry meets the requirements for chemical diversity and reactivity as compared to carbon. To expand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 234 publications
(316 reference statements)
0
47
0
1
Order By: Relevance
“…Under Earth conditions, however, silicon reacts both with water and molecular oxygen, and is quickly immobilized as silicates. Petkowski et al [75] explored silicon's chemical complexity in several solvents present in planetary environments such as water, cryosolvents, and sulfuric acid. They concluded that in no environment would life based primarily on silicon chemistry be a plausible option.…”
Section: Alternative Biochemistriesmentioning
confidence: 99%
“…Under Earth conditions, however, silicon reacts both with water and molecular oxygen, and is quickly immobilized as silicates. Petkowski et al [75] explored silicon's chemical complexity in several solvents present in planetary environments such as water, cryosolvents, and sulfuric acid. They concluded that in no environment would life based primarily on silicon chemistry be a plausible option.…”
Section: Alternative Biochemistriesmentioning
confidence: 99%
“…Some aromatic phosphines are highly stable in sulfuric acid, but there are few representatives of these in the datasets used here. More unexpected is the depletion of silicon-containing compounds, as our previous analysis [ 87 ] suggests that a greater diversity of organosilicon compounds should be stable in sulfuric acid than in water. We hypothesize that the relative instability of silicon compounds seen in Figure 7 is the result of the use of specific, selected silicon chemistry in organic synthesis, and is not representative of the more broad qualitative analysis of the stability of organosilicon chemistry done in [ 87 ].…”
Section: Resultsmentioning
confidence: 95%
“…More unexpected is the depletion of silicon-containing compounds, as our previous analysis [ 87 ] suggests that a greater diversity of organosilicon compounds should be stable in sulfuric acid than in water. We hypothesize that the relative instability of silicon compounds seen in Figure 7 is the result of the use of specific, selected silicon chemistry in organic synthesis, and is not representative of the more broad qualitative analysis of the stability of organosilicon chemistry done in [ 87 ]. Specifically, the large majority of silicon-containing compounds in the chemical dataset are trimethylsilyl ethers or compounds containing phenylsilyl groups, both of which are known to be acid-labile [ 97 , 98 ].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations